Effects of Glaucoma Treatment on Ocular Surface and Tear Functions: Comparison of Trabeculectomy and Antiglaucoma Drops - Abdussamet Mermer; Özer Dursun; Öznur Bucak; Hamide Sayar; Fatma Merve Bektaş; Pınar Eröz; Ayça Yılmaz (Türk Oftalmoloji Dergisi, 2024)
Objectives: To investigate tear function and ocular surface disease (OSD) findings in patients with glaucoma who received antiglaucoma medication in one eye and trabeculectomy surgery in the other eye. Materials and Methods: The patient group included 38 eyes of 19 patients who had undergone trabeculectomy surgery with mitomycin C (MMC) treatment in one eye at least 6 months prior. These eyes were followed up without medication while the fellow eye continued receiving antiglaucomatous medication. The control group comprised 20 eyes of 20 healthy individuals. Demographic data, follow-up period after trabeculectomy, antiglaucoma medications, number of drops per day, and duration of medication were recorded. Tear break-up time (BUT), corneal and conjunctival fluorescein staining, Schirmer II test, and conjunctival impression cytology were performed. Results: A statistically significant difference was observed in BUT, corneal and conjunctival fluorescein staining, Schirmer II test, and Nelson staging levels in both eyes of patients with glaucoma compared to the control group (p=0.05). Although not statistically significant, BUT, Schirmer II test, punctate staining, and Nelson staging results showed improvement with increasing postoperative time. Conclusion: In our patient group, antiglaucoma medications and trabeculectomy surgery with MMC induced OSD to a similar degree. No superiority was observed between trabeculectomy with MMC and antiglaucoma drops in terms of OSD incidence.